The Impact of Corporate Governance Adoption in Algeria on Activating the Role of the Board of Directors in Companies - A Field Study - taleb hacine, siham (Journal of Research in Finance and Accounting, 2024)
This study aims to assess the impact of adopting corporate governance in Algeria on enhancing the role of the Board of Directors in companies. The study first addresses the theoretical framework of corporate governance and the Board of Directors as a key mechanism, followed by an empirical study where we statistically analyzed the research problem using a sample from a group of Algerian economic companies. The study reached several conclusions, the most important of which is the positive impact of Algeria's efforts to adopt governance on activating the role of the Board of Directors. However, there are challenges that must be addressed to further enhance its role, aiming to improve institutional performance and build trust in companies.